The problem is not anonymity, but genocide; Reply to Babish’s “Response to the AnonymOT Collective”

(untitled) (University of Ottawa, 2025)
Babish’s response to our commentary, Occupational Therapists Speaking for Justice and Human Rights: From Complicit Silencing to Collective Resistance (AnonymOT Collective, 2024), contests the anonymity chosen by its authors, and contends that there is a paradox in anonymity in the context of justice. A “paradox” is something that appears self-contradictory but that may hold deeper truth. While appearing contradictory, the fact that anonymity can be used to serve justice could thus hold a certain truth. Our intentions in responding to Babish are to assert that justice can be advanced without centring one’s own identity, to assert our belief in the value of a diversity of tactics in the fight against oppression and injustice, and to affirm our commitment to stand in solidarity with the Palestinian people and with others who are similarly committed. Thus, we explicitly stand with Babish and their community in our intention – even if we may disagree on elements of praxis. We hope our reply is seen as complementary to, and supportive of his call to amplify the voices of Palestinians.